Stosowanie mediów cyfrowych w edukacji wyższej – konfrontacja opinii nauczycieli akademickich i studentów - Klimas, Patrycja (Studia Edukacyjne, 2018)
Recommendations made by policy makers, increasing competitive pressure and growing popularity of digital media among participants of teaching processes contribute to their increasingly extensive use at Polish universities. The fact that the teaching processes has entered the new, digital dimension reveals the need for information concerning the relevance of use of electronic media, especially from the perspective of achieving learning outcomes. Given the above, the purpose of this paper is to present results of research on opinions of both students and academics on the need and significanceof the application of digital media in the learning processes.For the purposes of the article, a quantitative research was conducted among 86 students and 66 teachers from University of Economics in Katowice. The data was collected in April 2015 using an online surveying technique and analyzed using statistical description.In the light of our results, the application of electronic media seems to not only be imposed by macro- and micro-environmental conditions, but also to be expected by the main participants of educational processes taking place at university level. The results show that both groups of respondents consider the use of digital media at least as advisable for the achievement of learning outcomes (71.8% of responses covered labels: advisable, recommended or required). However, the level of necessity is slightly higher when digital tools are used by students (80.7%) than by teachers (70.3%). In general, multimedia presentations have been identifiedas the most required form of digital media application in teaching at the university.